Trends in fertility rates, proportion of antenatal consultations and caesarean sections among Brazilian adolescents - Milena Laryssa Costa Bicalho; Fernanda Gontijo Araújo; Gisele Nepomuceno de Andrade; Eunice Francisca Martins; Mariana Santos Felisbino-Mendes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To analyze the temporal trends in the fertility rate, proportion of antenatal consultations and caesarean sections in Brazilian adolescents aged 15 to 19, between 2000 and 2015. Methods: The fertility rate, proportion of prenatal consultations and proportion of routes of birth were calculated using data from DATASUS. The trend analysis was performed using the Prais-Winsten regression model and the annual percentage change. Results: There was a trend of reduction of 3.5% per year in the fertility rate among adolescents (p<0.05), in addition to an increasing trend of 6% per year in the proportion of more than six antenatal consultations (p <0.0001) and an increasing trend of 6.8% per year in the proportion of caesarean sections (p<0.0001). Conclusion: Despite the decreasing trend in fertility rates among Brazilian adolescents, they remain high. Also noteworthy is the growing trend for caesarean sections, even with improved access to antenatal care.